Hemodialysis in the context of COVID-19: care, nursing protagonism and quality - Regina Bokehi Nigri; Renata Flávia Abreu da Silva (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To reflect on the need to reorganize satellite dialysis units to ensure the safety of patients and workers, focusing on minimizing the risk of contamination by SARS-CoV-2. Methods: Reflection considering the guidelines of international and Brazilian institutions and scientific articles, with a view to possible adaptations to the Brazilian reality. Results: The actions suggested and adapted by Dialysis Units from different countries during the pandemic focus on the quality of care and safety of the patient and workers. There was an opportunity to reflect on these actions using the Donabedian Model for quality of care and highlight the nursing team's role in this context. Final considerations: The focus on quality and safety related to institutionalized processes and the assessment through indicators can contribute to the management of the outpatient dialysis unit in the context of COVID 19.